Tapeworms (Cestoda: Proteocephalidae) of the gars (Lepisosteidae), living fossils in America, including proposal of a new genus and a new species - Scholz, Tomáš; de Chambrier, Alain; Kyslík, Jiří (Parasitology international, 2024)
A new genus, Cordicestus, is proposed to accommodate proteocephalid tapeworms parasitising gars (Lepisosteiformes: Lepisosteidae) in North and Central America that were previously placed in the polyphyletic genus Proteocephalus Weinland, 1858. The new genus differs from other proteocephalid genera by the particular morphology of the scolex, which is small, protrudes apically but has no apical organ, and bears flat, heart-shaped (= cordis) suckers. In addition, the species of the new genus have an elongated cirrus sac with an almost straight internal vas deferens and wide, sinuous ventral osmoregulatory canals with secondary canals directed outwards. The type species of the new genus, Cordicestus singularis (La Rue, 1911) n. comb., is redescribed based on new material from the shortnose gar, Lepisosteus platostomus Rafinesque (type host), and the spotted gar, L. oculatus Winchell, in the United States. Cordicestus rafaeli n. sp. is described from the tropical gar, Atractosteus tropicus Gill, in Mexico. The new species differs from its relatives primarily by the presence of craspedote proglottids (acraspedote in other species) and some biometric features. All species of Cordicestus are revised, including unidentified specimens from A. tropicus and the Cuban gar A. tristoechus (Bloch and Schneider) in Nicaragua and Cuba, respectively, which may be new species, and a key to the identification of these taxa is provided. Molecular data available for two nominal species of the new genus indicate the possible existence of another species of Cordicestus in Lepisosteus in the USA.
Keywords: zkameněliny; Taxonomy; Tapeworms; North and Central America; United States; Lepisosteiformes; cestodózy; Morphology; Fossils; Scolex; zvířata; nemoci ryb; Spojené státy americké; Střední Amerika; fylogeneze; Redescription; Central America; Cestoda; Fish Diseases; Fishes; ryby; Cestode Infections; Phylogeny; Animals